Performance simulation of a power-water combined plant driven by low grade waste heat. (1st August 2017) - He, W.F.; Zhu, W.P.; Han, D.; Huang, L.; Wu, Y.K.; Zhang, X.K.
Highlights: A novel combined plant is proposed to produce power and water simultaneously. Mathematical models of the combined plant are established. Performance of the combined plant at designed conditions is simulated iteratively. Influence principles from the condensing temperature and pinch temperature difference are calculation and revealed. Abstract: Both power and freshwater are obligatory for life and industry production. The present paper suggested a novel power-water combined plant (PWCP) driven by low grade waste heat to supply power and water simultaneously, in which the organic Rankine cycle (ORC) and air-heated humidification dehumidification (HDH) desalination subsystem are coupled. Through the connection effect of the condenser for the ORC power subsystem, mathematical models of the combined plant are presented. The relevant performance of the combined plant at the designed conditions is simulated iteratively, and the influences from the condensing temperature and pinch temperature difference (PTD) are investigated. The simulated results show that the peak value of the output power arrives at Wnet  = 14.90 kW when the evaporation temperature of R123 is T 1  = 401.15 K. Based on the conditions at the maximum power case of the ORC, the maximum freshwater production reaches mfw  = 381.66 kg h −1 at the balance condition of the dehumidifier, HCRd  = 1 at msw  = 2.9 kg s −1 . Accordingly, the peak value of the gained output ratio (GOR), GOR  = 1.93, also indicates the best energy utilization situation within the HDH desalination system at HCRd  = 1. After the regulation of the condensing temperature as well as pinch temperature difference of the ORC subsystem, a peak value of power for the ORC system, Wnet  = 16.56 kW at T 3  = 338.15 K, and maximum value of the freshwater production, mfw  = 381.66 kg h −1 at T 3  = 343.15 K are obtained.